Microarchitectural study of the olfactory organ of Devario regina (Fowler, 1934) using pas technique - Boonyoung, Piyakorn; Senarat, Sinlapachai; Kettratad, Jes; Yenchum, Watiporn; Poolprasert, Pisit; Jiraungkoorskul, Wannee (Journal of Bio-Science, 2016)
Context: Microarchitectural observation of the olfactory organ in Devario regina (Fowler, 1934) is still unknown. Objectives: The normal histology and chemical detailed of glycoprotein in D. regina olfactory organ were investigated using histochemical analysis. Materials and Methods: Fishes were collected from the Tapee River, Nakhon Si Thammarat Province, Thailand and were processed by the standard histological technique. Results: Microarchitecture of olfactory organ revealed that it was a paired olfactory sac. Each sac was composed of the olfactory chamber and many lamellae surrounding by olfactory epithelium. This epithelium contained the differential cell types in both sensory (sensory ciliated cells) and non-sensory olfactory epithelium. The special localization of glycoprotein was intensively detected on the mucous cells. Conclusion: This study provided the basic histology of the fish olfactory organ that will support the investigation regarding the physiological and ultrastructural analysis. J. bio-sci. 22: 41-44, 2014